Efektivitas Metode Drill terhadap Kemampuan Sintaksis pada Anak Autism Spectrum Disorder di Karesidenan Surakarta - Avrilla, Sefanya; Muryanti, Muryanti; Susanti, Nadya (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Abstract Autism Spectrum Disorder (ASD) is a developmental disorder that affects communication, social interaction, and behavior, with signs of difficulty understanding and using language verbally or nonverbally. The language ability of children with autism is different from other children, the syntactic pattern is still simple, often only mentioning phrases in saying something so that they are not able to make meaningful sentences. The prevalence of children with autism in Surakarta City reaches 100 children and is the second highest number of autistic students in Central Java. Objectives: This study aims to determine the effectiveness of the drill method on syntactic abilities in ASD. Methods: The type of research to be conducted is quantitative research with the method used, namely pre- experimental with One Group Pre-test Post-test Design. The number of samples used was 15 children with ASD. The collected data will be analyzed descriptively and bivariously using a statistical test technique, namely the Wilcoxon Signed Rank Test. Results: Based on the pre-test and post-test bivariate tests that have been carried out on 15 ASD children, the results show that the pretest posttest score was obtained with a Z value of -3.334 and an Asymp.Sig (2-tailed) value of 0.001. Because the value is 0.001 < 0.05, Ho is rejected and Ha is accepted. Conclusion: After receiving treatment 12 times, it was found that the average increase in the test score from 12.40 to 16.20 based on the results of the analysis test with the Wilcoxon Signed Ranks Test obtained a p value (sig.) of 0.001 or a p value (sig.) <0.05. So it can be interpreted that there is an increase in syntactic ability using the drill method in children with autism spectrum disorder. Keywords: Drill Method, Autism, Syntactic Ability